Engineering Toxin‐Resistant Therapeutic Stem Cells to Treat Brain Tumors. (22nd January 2015) - Stuckey, Daniel W.; Hingtgen, Shawn D.; Karakas, Nihal; Rich, Benjamin E.; Shah, Khalid
Abstract : Pseudomonas exotoxin (PE) potently blocks protein synthesis by catalyzing the inactivation of elongation factor‐2 (EF‐2). Targeted PE‐cytotoxins have been used as antitumor agents, although their effective clinical translation in solid tumors has been confounded by off‐target delivery, systemic toxicity, and short chemotherapeutic half‐life. To overcome these limitations, we have created toxin‐resistant stem cells by modifying endogenous EF‐2, and engineered them to secrete PE‐cytotoxins that target specifically expressed (interleukin‐13 receptor subunit alpha‐2) or overexpressed (epidermal growth factor receptor) in glioblastomas (GBM). Molecular analysis correlated efficacy of PE‐targeted cytotoxins with levels of cognate receptor expression, and optical imaging was applied to simultaneously track the kinetics of protein synthesis inhibition and GBM cell viability in vivo. The release of IL13‐PE from biodegradable synthetic extracellular matrix (sECM) encapsulated stem cells in a clinically relevant GBM resection model led to increased long‐term survival of mice compared to IL13‐PE protein infusion. Moreover, multiple patient‐derived GBM lines responded to treatment, underscoring its clinical relevance. In sum, integrating stem cell‐based engineering, multimodal imaging, and delivery of PE‐cytotoxins in a clinically relevant GBM model represents a novel strategy and a potential advancement in GBM therapy. Stem Cells   2015;33:589–600